1996
DOI: 10.1002/mrm.1910350412
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of primary liver cancer in rats by MS‐264‐enhanced MRI

Abstract: A new MR contrast agent, MS-264 (Gd(1RS)-1-(p-butylbenzyl)-DTPA), was developed to achieve hepatobiliary specificity and its potential evaluated for detecting and characterizing liver tumors in rats with chemically induced hepatocellular carcinoma (HCC). In seven rats with 66 HCC lesions, enhancements of different abdominal organs and tumors were compared on T1-weighted images after intravenous administration of Gd-DTPA (0.3 mmol/kg) and MS-264 (0.05 mmol/kg). MR images were correlated with postmortem microang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Such TCE never appears with nonspecific CAs such as Gd-DTPA. After investigating over hundred accumulated animal tumors, we were the first to publish such findings in order to draw public attentions to their potential for differential diagnosis of focal liver lesions [11][12][13]15]. However, by studying only 31 patients without positive TCE encountered, Vogl et al in their first clinical report attempted to challenge our initial findings and concluded that similar to Gd-DTPA, Gd-EOB-DTPA could not provide ''differential diagnostic information" [64].…”
Section: +mentioning
confidence: 90%
See 2 more Smart Citations
“…Such TCE never appears with nonspecific CAs such as Gd-DTPA. After investigating over hundred accumulated animal tumors, we were the first to publish such findings in order to draw public attentions to their potential for differential diagnosis of focal liver lesions [11][12][13]15]. However, by studying only 31 patients without positive TCE encountered, Vogl et al in their first clinical report attempted to challenge our initial findings and concluded that similar to Gd-DTPA, Gd-EOB-DTPA could not provide ''differential diagnostic information" [64].…”
Section: +mentioning
confidence: 90%
“…MRI prior to I but overnight post Mn-DPDP injection in J, normal liver lobes (NL) showed contrast clearance but CE persisted in the ligated lobes (BL), supporting the proposed mechanisms for positive TCE and rim-CE with Mn-DPDP. normal hepatocytes and liver tumors of various origins and grades [11][12][13]15]. Comparing to Mn-DPDP, these hepatobiliary CAs also showed positive, negative and rim TCE but in quite dissimilar tumor differentiation spectra (Table 3).…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Liver imaging of rats with chemically induced hepatocellular carcinoma (HCC) resulted in a higher relative enhancement of normal liver tissue as compared with Gd-DTPA alone or no contrast. Of the 66 HCCs detected, 59 showed negative contrast enhancement and 6 positive enhancement [22].…”
Section: Liver Agentsmentioning
confidence: 99%
“…Chelates with lipophilic components were investigated as potentially liver-specific compounds (VITTADINI et al 1988;WEINMANN et al 1991;SCHUHMANN-GIAMPIERI et al 1992;PETRE et al 1995;RUNGE and WELLS 1995). All hepatocytespecific agents are ionic metal chelates and, unlike many other hepatotropic compounds, display a relatively pronounced hydrophilicity.…”
Section: Hepatobi/iary Gadolinium Chelatesmentioning
confidence: 99%